Implementation of the Micro-Scale Profit-Sharing Principle: Ethnography of Islamic Arisan and Farmer Group Financing in Rural Java - Muhammad An Naufar Prastyo; Yeni Maratus Solekah (Al-Muamalat: Journal of Islamic Economics Law, 2025)
ENGLISH This ethnographic study examines the implementation of the profit-sharing principle at the micro level in two traditional financial schemes in rural Java: Islamic arisan (social savings) and musharaka-based farmer group financing. The issues raised relate to the difficulties formal Islamic microfinance institutions face in implementing profit-sharing contracts, while informal community financial practices have successfully implemented this principle for generations but have been under-researched. The methods used include participant observation over twelve months (July 2024–June 2025) in Taji Village, Karas District, Magetan Regency, East Java, semi-structured interviews with sixty-eight informants, observations of forty-eight arisan meetings and twenty-two cooperative farming activities, and analysis of group financial documents. Data were analyzed through thematic coding and re-verified through member checking and validation based on Islamic jurisprudence (fiqh muamalah). The results show that Islamic arisan applies a one-to-one ratio based on qardh hasan with a selapan cycle and open accountability rituals, while the farmer group uses a double musharakah model, namely a fifty percent profit sharing when the farmer only provides labor and seventy-thirty percent when the landowner also bears input costs. The community murāqabah mechanism through social sanctions and deliberation decisions effectively replaces written contracts. Both schemes recorded a zero percent arrears rate, a thirty-two percent increase in average income for arisan participants, and a forty-five percent decrease in irrigation conflicts. The novelty of the study lies in the conceptualization of community murāqabah as an informal monitoring mechanism and the integration of Javanese mutual cooperation values with sharia principles. The practical implications emphasize the need to formalize traditional mechanisms as wadiah yad dhamanah products in Baitul Maal wa Tamwil to expand sharia microfinance inclusion. INDONESIA Penelitian etnografis ini mengkaji implementasi prinsip bagi hasil dalam skala mikro pada dua skema keuangan tradisional di pedesaan Jawa, yakni arisan syariah dan pembiayaan kelompok tani berbasis musyarakah. Permasalahan yang diangkat berkaitan dengan kesulitan lembaga mikrofinansial syariah formal menerapkan kontrak bagi hasil, sementara praktik keuangan komunitas informal telah berhasil menjalankan prinsip tersebut secara turun temurun namun kurang diteliti. Metode yang digunakan meliputi observasi partisipan selama dua belas bulan (Juli 2024–Juni 2025) di Desa Taji Kecamatan Karas Kabupaten Magetan Jawa Timur, wawancara semi terstruktur dengan enam puluh delapan informan, pengamatan empat puluh delapan pertemuan arisan dan dua puluh dua kegiatan pertanian bergotong royong, serta analisis dokumen keuangan kelompok. Data dianalisis melalui pengodean tematik dan diverifikasi kembali melalui member checking serta validasi fiqh muamalah. Hasil menunjukkan bahwa arisan syariah menerapkan nisbah satu banding satu berdasarkan qardh hasan dengan siklus selapan dan ritual akuntabilitas terbuka, sedangkan kelompok tani menggunakan model musyarakah ganda yaitu pembagian hasil lima puluh persen saat petani hanya menyediakan tenaga dan tujuh puluh tiga puluh persen saat pemilik lahan juga menanggung biaya input. Mekanisme murāqabah komunitas melalui sanksi sosial dan keputusan musyawarah efektif menggantikan kontrak tertulis. Kedua skema mencatat angka tunggakan nol persen, peningkatan pendapatan rata rata tiga puluh dua persen bagi peserta arisan, serta penurunan konflik irigasi empat puluh lima persen. Kebaruan penelitian terletak pada konseptualisasi murāqabah komunitas sebagai mekanisme pengawasan informal dan integrasi nilai gotong royong Jawa dengan prinsip syariah. Implikasi praktisnya menegaskan perlunya memformalkan mekanisme tradisional sebagai produk wadiah yad dhamanah di Baitul Maal wa Tamwil untuk memperluas inklusi keuangan mikro syariah.